Add <math><mstyle displaystyle="true"><mn>7</mn><mi>y</mi></mstyle></math> and <math><mstyle displaystyle="true"><mn>3</mn><mi>y</mi></mstyle></math> .

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>4</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>9</mn><mi>y</mi></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>9</mn><mi>y</mi></mstyle></math> from <math><mstyle displaystyle="true"><mn>10</mn><mi>y</mi></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Do you know how to Solve for y 7y-4+3y+6=9y+8? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.